Perencanaan Ulang Tata Letak dan Kebutuhan Apar Pada Pabrik Karung Plastik - Ayomi Nur Laili; Moch. Luqman Ashari; Fiqih Kurniasandy; Syeida Rusyda Bariroh (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Abstract This study discusses the re-planning of the layout of Light Fire Extinguishers (APAR) in plastic sack factories with the aim of increasing effectiveness and efficiency in dealing with fire risks. Availability of proper fire extinguishers and optimal layout is very important in maintaining security and safety in the plastic sack factory environment. This study uses a field survey method to understand the condition of the plastic sack factory and analyze the risk of fire that might occur. Factors such as accessibility, mileage, number and type of fire extinguishers needed, as well as safety regulations and standards are considered in planning a more efficient fire extinguisher layout. The results of this study provide concrete and implementable recommendations regarding re-planning the layout of fire extinguishers at plastic sack factories. This recommendation is expected to assist plastic bag factory managers in increasing the level of security and preparedness in dealing with the risk of fire. It is hoped that the implementation of this fire extinguisher layout re-planning will strengthen the safety system of the plastic sack factory and reduce potential losses due to fire. This research can also be the basis for further research in the field of APAR layout planning in other industries that have similar fire risks. Abstrak Penelitian ini membahas tentang perencanaan ulang tata letak Alat Pemadam Api Ringan (APAR) pada pabrik karung plastik dengan tujuan untuk meningkatkan efektivitas dan efisiensi dalam menghadapi risiko kebakaran. Ketersediaan APAR yang tepat dan tata letak yang optimal sangat penting dalam menjaga keamanan dan keselamatan di lingkungan pabrik karung plastik. Penelitian ini menggunakan metode survei lapangan untuk memahami kondisi pabrik karung plastik dan analisis risiko kebakaran yang mungkin terjadi. Faktor-faktor seperti aksesibilitas, jarak tempuh, jumlah dan jenis APAR yang diperlukan, serta regulasi dan standar keamanan dipertimbangkan dalam merencanakan tata letak APAR yang lebih efisien. Hasil dari penelitian ini memberikan rekomendasi konkret dan implementatif mengenai perencanaan ulang tata letak APAR pada pabrik karung plastik. Rekomendasi ini diharapkan dapat membantu para pengelola pabrik karung plastik dalam meningkatkan tingkat keamanan dan kesiapan dalam menghadapi risiko kebakaran. Diharapkan bahwa implementasi perencanaan ulang tata letak APAR ini akan memperkuat sistem keamanan pabrik karung plastik dan mengurangi potensi kerugian akibat kebakaran. Penelitian ini juga dapat menjadi dasar untuk penelitian lebih lanjut dalam bidang perencanaan tata letak APAR di industri-industri lain yang memiliki risiko kebakaran serupa. Kata kunci: APAR, risiko kebakaran, pabrik karung plastik